“Braços para o trabalho”: mortalidade infantil e políticas de higiene em Fortaleza (1892-1928) - Barros, Karla Torquato dos Anjos (2019)
In this research, we analyze the discourses about hygiene produced by intellectuals of Ceará, in an attempt to guide policies to combat child mortality in Fortaleza during the first republican decades. For the purpose of examining these discourses, we look at a varied set of reports, messages, magazines, articles and journals produced by intellectuals, doctors, engineers and politicians between the years of 1892 and 1928, during which time the health services were in charge of the state power, and then the local professionals have a greater role in the mapping of needs, elaboration of plans and actions to address the problem of child mortality in the capital of Ceará. We investigate this material considering its context of production; the way discourses were structured; the conceptions on which they were based; the interests at stake when they were published and the purposes of their production. We then grouped these reports, making possible comparisons, the establishment of contrasts and the perception of possible articulations between these sources. Thus, we were able to follow first the process of elaborating a problematic about child mortality in the capital of Ceará, in the Republican context, in which the national projects defended by the Ceará intelligents were strongly linked to the increasing valorization of the workforce, and in which the high rates of child mortality in the city came to be increasingly seen as an obstacle to Ceará's progress. We then focused on the discussion of gastrointestinal diseases, given that they were primarily responsible for high child mortality rates. Finally, as the development of these diseases among children was pointed out as a result of poor quality of food and lack of urban sanitation, we then discussed the discussions about breastfeeding and the introduction of solid foods in children's diets, as well as the ways of water supply in the city and the sewage systems used by the population of Fortaleza